REARRANGEMENT OF ADMINISTRATIVE BOUNDARIES FOR REDUCING INNER-CITY DISPARITY: CASE STUDY OF TANJUNG PINANG CITY, INDONESIA - Adjie PAMUNGKAS (Journal of Urban and Regional Analysis, 2017)
An imbalance in development between islands in Tanjung Pinang City causes inner-city disparities due to insufficient development strategies, lack of public infrastructure and remoteness of islands. On the other hand, properly designed administrative boundaries can reduce inner-city disparities by enabling good development strategies, prioritizing public infrastructure development, and connecting the entire area, including remoter islands. This paper discusses how to re-arrange administrative boundaries, particularly at the district and sub-district levels in order to decrease inner-city disparities. A combination method of scoring and participatory mapping is used to suggest new district delineation for the city. After considering the outputs of scoring and participatory mapping, the district boundaries were changed from four to eight and then back to six districts. The paper also proposes key development strategies to boost development in poorer districts by improving the allocation of new infrastructure investment so as to optimize the impact of new municipal and provincial government statuses bestowed on the Dompak and Senggarang Districts. In addition, we suggest that development strategies should provide adequate infrastructure to connect remoter islands in the Penyengat Sub-district to the main island.